Ideal Cereals With Lower Arsenic and Cadmium by Accurately Enhancing Vacuolar Sequestration Capacity - Deng, Fenglin; Yu, Min; Martinoia, Enrico; Song, Won-Yong (Frontiers in Genetics, 2019)
Cereals are a staple food for many people around the world; however, they are also a major dietary source of toxic metal(loid)s. Many agricultural regions throughout the world are contaminated with toxic metal(loid)s, which can accumulate to high levels in the grains of cereals cultivated in these regions, posing serious health risks to consumers. Arsenic (As) and cadmium (Cd) are efficiently accumulated in cereals through metal transport pathways. Therefore, there is an urgent need to develop crops that contain greatly reduced levels of toxic metal(loid)s. Vacuolar sequestration of toxic metal(loid)s is a primary strategy for reducing toxic metal(loid)s in grains. However, until recently, detailed strategies and mechanisms for reducing toxic metal(loid)s in grain were limited by the lack of experimental data. New strategies to reduce As and Cd in grain by enhancing vacuolar sequestration in specific tissues are critical to develop crops that lower the daily intake of As and Cd, potentially improving human health. This review provides insights and strategies for developing crops with strongly reduced amounts of toxic metal(loid)s without jeopardizing agronomic traits.